Left atrial myxoma with concomitant coronary artery stenosis: comprehensive diagnosis and treatment - Erwin Ciechański; Krystian Ciechański; Jarosław Szponar; Piotr Kołątaj; Marcin Szczasny; Andrzej Głowniak; Justyna Szumiło (Kazimierz Wielki University, 2022)
A 69-year-old patient was admitted to the Department of Cardiology due to an accidental finding on a chest X-ray, enlarged heart outline, accompanied by worsening of heart failure to NYHA II with LVEF, about 30%. In the X-ray description, an enlargement of the left atrium silhouette with local calcifications. The patient underwent TTE, confirming the presence of a pedunculated tumor of the left atrium attached to the ceiling measuring 3.5x3.5x2.2 cm. Due to the ischemic heart disease manifestation patient uderwent coronarography confirming the presence of single-vessel coronary artery disease with changes in the middle segment of the LAD. Patient was treated with CABG LIMA-LAD surgery and removeal the left atrial tumor. Post operation tissue material prooved the preseance of left atrium myxoma. The postoperative course was uneventful, the patient was discharged home.